PERAN ORANGTUA DALAM MEMBANGUN KARAKTER RELIGIUS ANAK DI KECAMATAN TRUCUK KABUPATEN BOJONEGORO - Siti Khoiriyah; Khoirotus Silfiyah (UNZAH Genggong, 2023)
Parents occupy a central role in the formation of character in children. Because the first environment occupied by children is the family environment. So that parents as the first teachers for children must have awareness and capacity in shaping, building and fostering children's character. Religious character is one of the 18 characters that must be possessed by the indonesian generation. The fading of the religious character of the nation's children must be of particular concern to parents. The method in this research is descriptive qualitative. The results of this study show the role of the family in building the religious character of children in trucuk sub-district, bojonegoro regency 1) through education and teaching in the family environment, 2) through role models in behaving in the family environment. 3) through regular habituation in the family environment. 4) through motivation by giving awards for children's achievements and giving warnings, reprimands or punishments for child carelessness or mistakes. Kaywords: Roles, Parents, Religious Characters Parents occupy a central role in the formation of character in children. Because the first environment occupied by children is the family environment. So that parents as the first teachers for children must have awareness and capacity in shaping, building and fostering children's character. Religious character is one of the 18 characters that must be possessed by the indonesian generation. The fading of the religious character of the nation's children must be of particular concern to parents. The method in this research is descriptive qualitative. The results of this study show the role of the family in building the religious character of children in trucuk sub-district, bojonegoro regency 1) through education and teaching in the family environment, 2) through role models in behaving in the family environment. 3) through regular habituation in the family environment. 4) through motivation by giving awards for children's achievements and giving warnings, reprimands or punishments for child carelessness or mistakes. Kaywords: Roles, Parents, Religious Characters